2015
DOI: 10.4012/dmj.2015-197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dentinal and apical crack formation caused by four different nickel-titanium rotary and reciprocating systems in large and small canals

Abstract: This study compared dentinal and apical crack formation after instrumentation with different nickel-titanium systems at two different working lengths (WL) in large and small canals. Two hundred and eighty human teeth were randomly distributed into two control and 12 experimental groups (n=20 each). Large and small canals were instrumented by the WaveOne, Protaper Universal System (PTU), Twisted File (TF), or Twisted File Adaptive (TFA) at 1 mm shorter than canal length (CL−1 mm) or 1 mm beyond apical foreman (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…Of those studies, 12 were excluded after we examined the full text because they did not conform to the eligibility criteria of this review, as shown in Table 2 20,30-40) . Finally, the 8 studies that met the inclusion criteria were included [21][22][23][24][25][26][27][28] . The process involved in the study selection is shown in Fig.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Of those studies, 12 were excluded after we examined the full text because they did not conform to the eligibility criteria of this review, as shown in Table 2 20,30-40) . Finally, the 8 studies that met the inclusion criteria were included [21][22][23][24][25][26][27][28] . The process involved in the study selection is shown in Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…Two studies 23,27) compared ProTaper and Reciproc. Five studies 22,[24][25][26]28) compared ProTaper and WaveOne. One study included both of the two comparison groups 21) .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Çalışmamızda en fazla dentin defekti, Reciproc grubunda tespit edilmiştir ve bu sonuç, Bürklein ve arkadaşlarının 8 bulguları ile benzerlik göstermektedir. TFA ile kök kanal şekillendirilmesinin dentin çatlakları üzerindeki etkisi birçok çalışmada değerlendirilmiştir 26,27. Çalışma bulgularımız, TFA ve kontrol gruplarında dentin defekti oluşumu tespit edilmeyen Zhou ve arkadaşlarının 23 bulguları ile uyumludur.…”
Section: Tfa Grubuunclassified